Intravenous magnesium in chronic obstructive pulmonary disease. Issue 2 (26th February 2004) - Jenner, Rachel; Body, Richard
Abstract : A short cut review was carried out to establish whether the addition of intravenous magnesium to standard treatments improved outcome in patients with exacerbations of COPD. Altogether 465 papers were found using the reported search, of which one presented the best evidence to answer the clinical question. The author, date and country of publication, patient group studied, study type, relevant outcomes, results, and study weaknesses of this best paper are tabulated. A clinical bottom line is stated.